Expressing the Thermoanaerobacterium saccharolyticum pforA in engineered Clostridium thermocellum improves ethanol production - Hon, Shuen; Holwerda, Evert K.; Worthen, Robert S.; Maloney, Marybeth I.; Tian, Liang; Cui, Jingxuan; Lin, Paul P.; Lynd, Lee R.; Olson, Daniel G. (Biotechnology for biofuels, 2018)
has been the subject of multiple metabolic engineering strategies to improve its ability to ferment cellulose to ethanol, with varying degrees of success. For ethanol production in , the conversion of pyruvate to acetyl-CoA is catalyzed primarily by the pyruvate ferredoxin oxidoreductase (PFOR) pathway. , which was previously engineered to produce ethanol of high yield (> 80%) and titer (70 g/L), also uses a pyruvate ferredoxin oxidoreductase, , for ethanol production. Here, we introduced the and ferredoxin into . The introduction of resulted in significant improvements to ethanol yield and titer in grown on 50 g/L of cellobiose, but only when four other genes ( , , , and ) were also present. ferredoxin did not have any observable impact on ethanol production. The improvement to ethanol production was sustained even when all annotated native genes were deleted. On high cellulose concentrations, the maximum ethanol titer achieved by this engineered strain from 100 g/L Avicel was 25 g/L, compared to 22 g/L for the reference strain, LL1319 ( ( )- ( )- ( )) under similar conditions. In addition, we also observed that deletion of the results in a significant decrease in isobutanol production. Here, we demonstrate that the gene can improve ethanol production in as part of the pyruvate-to-ethanol pathway. In our previous strain, high-yield (~ 75% of theoretical) ethanol production could be achieved with at most 20 g/L substrate. In this strain, high-yield ethanol production can be achieved up to 50 g/L substrate. Furthermore, the introduction of increased the maximum titer by 14%.